PREHEATER CHARACTERISTICS OF INDIRECT INJECTION DIESEL ENGINE USING PURE COCONUT OIL (Cocos nucifera L.) AND PURE TAMANU OIL (Calophyllum inophyllum L.) - Putri Permatasari, Dini
Pure plant oil (PPO) is one alternative fuel source that can be used by diesel motors. The use of PPO as fuel is still hampered by the high value of viscosity, therefore it is necessary to modify the diesel motor with using of a preheater. The preheater is designed by utilizing heat from the exhaust gas to heat PPO with the working principle of a helical coil heat exchanger. Preheater characteristics are known by conducting performance tests before and after the endurance test of indirect injection diesel engine and the influence of smoke opacity emissions on diesel motor exhaust gases. In this research obtained that pure coconut oil (PCO) could use as fuel and reaching the highest load of 3200 W by heating it to a temperature of 184.8oC, while pure tamanu oil (PTO) could be used up to the highest load of 4000W by heating it to a temperature of 95.7oC. The average smoke opacity emissions on the use of PCO fuel before the endurance test on an indirect injection diesel engine was 16.29% and after an endurance test on an indirect injection diesel engine was 30.46%. In the use of PTO the average smoke opacity emissions before the endurance test on an indirect injection diesel engine was 6.37% and after an endurance test on an indirect injection diesel engine was 9.98%. As a result, the average thickness of the deposit on the coil and wall in the cylinder with the use of PCO fuel was greater 3.13 ?m and 410 ?m than using of PTO fuel. This is because PTO has a greater heating value and cetane number, so that the combustion that occurs is more optimal. Based on the test results it was found that PCO and PTO could be used as biofuels in indirect injection diesel engine. Furthermore, it is concluded that the use of PTO that has been preheated as an indirect injection diesel engine is better than using PCO.